Incidence of childhood tumours in Queensland. - McWhirter, W. R. (Nature Publishing Group, 1981)
The incidence of childhood cancer in Queensland has been studied using the data of the population-based Queensland Childhood Malignancy Registry. During the 7-year period 1973-1979, 454 cases were registered, giving an annual age-specific incidence of 11.34/10(5) for the age group 0-14 years inclusive. There was a male/female ratio of 1.36. The commonest group of diseases was that of the leukaemias, followed by that of CNS tumours. The incidences of the various types of tumour in Queensland have been compared with those from other reported series. The incidence of leukaemia was midway between that of U.S. whites and that of Manchester, while the incidences of lymphoma and Wilms' tumour were much closer to those of the United States. Ewing's tumour was considerably commoner than osteosarcoma.